Does your Journal meet your requirements? - Doubell, Anton (SA Heart Journal, 2017)
SA Heart Journal: Does the Journal keep you up to date with new developments in the field of cardiology and cardiac surgery? Does publication in the Journal provide you with a publication listed by the Department of Health, providing subsidy for the academic institution you work for? Incidentally, the answer to this last question is yes! Does the Journal keep you up to date with the affairs of the South African Heart Association? Does the Journal regularly improve your ECG knowledge? Does the Journal regularly improve your echocardiography knowledge? Do you read the Journal? Do you enjoy reading the Journal? Do you read the electronic version of the Journal or do you prefer receiving the printed version (the number of printed copies distributed was recently reduced to combat the rising cost of producing the Journal). Does the Journal add value to the publication of scientific information in South Africa?